Second Language Acquisition : Pedagogies, Practices and Perspectives - Savvidou, Christine; Savvidou, Christine (IntechOpen, 2020)
This volume presents a collection of current research on pedagogies, practices and perspectives in the field of second language acquisition. It brings together different aspects of learning, teaching and researching a second language with chapters covering a range of topics from emotional communication, pragmatic competence, transformative pedagogy, inclusion, reflective teaching and innovative research methodologies. The authors address a global audience to offer insights into contemporary theories, research, policies and practices in second language acquisition. This collection of work is aimed at students, teachers and researchers wishing to reflect on current developments and identify potential research directions.
English
Keywords: Educational psychology; Educational psychology